The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3989/ajbm.2004.v61.i1.61
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Colletotrichum acutatum is major pathogen of fruit crops, causing economically important losses of temperate, subtropical and tropical fruits worldwide. However, few studies have been carried out on key aspects of its biology. This is mainly because traditionally isolates of C. acutatum were often wrongly identified as C. gloeosporioides. Effective separation of the two species was not possible until the introduction of molecular tools for taxonomy. The life cycle of C. acutatum comprises a sexual and an asexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 95 publications
0
15
0
3
Order By: Relevance
“…Thus, the development of the infection can be observed as the fruit ripens. However, in our experimental setting, we observed that at 1 h post inoculation, the fruit is highly resistant probably due to the presence of antifungal compounds (Table 2) (Yakoby et al, 2002; Wharton and Diéguez-Uribeondo, 2004; Prusky and Lichter, 2007). By contrast, in the presence of chitosan and the pathogen (QP), there is a strong defense response even at 24 h post-inoculation (Table 2).…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the development of the infection can be observed as the fruit ripens. However, in our experimental setting, we observed that at 1 h post inoculation, the fruit is highly resistant probably due to the presence of antifungal compounds (Table 2) (Yakoby et al, 2002; Wharton and Diéguez-Uribeondo, 2004; Prusky and Lichter, 2007). By contrast, in the presence of chitosan and the pathogen (QP), there is a strong defense response even at 24 h post-inoculation (Table 2).…”
Section: Discussionmentioning
confidence: 79%
“…With respect to fruit infection, the early stages of the interaction with host tissues are similar for all the Colletotrichum species [ 7 ]: conidiospores spread from infected vegetal material or through insects, adhere by means of a hemicellulosic mucilage to the external vegetal surface, germinate and infect often by mean of specialized structures, such as appressoria [ 8 , 9 , 10 , 11 ]. Infections can take place even by penetration through stomata, lenticels, wounds, or abscission of scar tissue [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Epidemiology and Pathology Of Colletotrichum Sppmentioning
confidence: 99%
“…The phenotypes of the obtained pure cultures of the isolates were documented, and hyphal and spore samples, when available, were microscopically examined. The tentative identification of the isolates was performed based on the phenotypic characteristics of the conidia and that of the cultures (shape, color and density of hyphae) using taxonomic keys [39].…”
Section: Phenotyping Tentative and Absolute Identification Of Fungal Isolatesmentioning
confidence: 99%